Severe myocarditis of possible human herpesviruses and 7 etiology in an 8-year-old immunocompetent child - Jaworski, Radosław; Pręgowska, Katarzyna; Kasztelewicz, Beata; Kowalczyk-Domagała, Monika; Kansy, Andrzej; Brzezińska-Rajszys, Grażyna; Dzierżanowska-Fangrat, Katarzyna (Pediatria Polska - Polish Journal of Paediatrics, 2021)
In this paper we present a case of an 8-year-old immunocompetent boy with acute myocarditis caused probably by concomitant human herpesvirus 6 (HHV-6) with human herpesvirus 7 (HHV-7) infection. The clinical manifestation included flu-like symptoms and fulminant heart failure, which required admission to an intensive care setting. Aggressive supportive heart failure management with administration of inotropes and antiviral and antibacterial treatment were applied. After implementation of therapy, the gradual improvement of heart function and patient’s condition was observed and the patient did not require Extracorporeal Membrane Oxygenation (ECMO) support. Two months after the symptoms’ onset, the patient was discharged home in a good general condition.